Factors Influencing Financial Distress and Its Impact on Company Values of the Sub-Sectors Firms in Indonesian - Murtadha, Milla Alsura; Arfan, Muhammad; Saputra, Mulia (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective The purpose of this study is to determine the influence of corporate governance, profitability, and firm size on financial distress and its impact to the company value of the sub-sectors companies in infrastructure, utilities, and transportation that are listed in Indonesia Stock Exchange for the period of 2011-2015.Design/methodology The secondary data in the form of financial statements are collected from the sub-sector companies in infrastructure, utilities, and transportation thand from the Indonesian Capital Market Directory (ICMD). The data is taken from the companies listed in Indonesia Stock Exchange in period of 2011-2015. Samples are determined by using purposive sampling method and the samples are selected based on certain considerations or criteria. The analysis model used in this study is path analysis.Results The results show that in the first line; corporate governance, profitability and firm size, both partially and simultaneously have significant influence on financial distress of the sub-sector companies on infrastructure, utilities, and transportation that are listed in Indonesia Stock Exchange. In the second track, corporate governance, profitability, firm size and financial distress both partially and simultaneously have significant influence on the company value in the sub-sectors of infrastructure, utilities, and transportation that are listed in Indonesia Stock Exchange.Research limitations/implications The time of observation of the study is only 5 years and it does not properly reflect the actual phenomenon. The samples of the study are only limited to Sub-Sector companies in Infrastructure, Utilities, Transportation even though there are still many other companies that are listed in Indonesia Stock Exchange.